KAJIAN YURIDIS PELIMPAHAN KEWENANGAN MONOPOLI NEGARA DALAM PENYELENGGARAAN JAMINAN SOSIAL - Dewi Cahyandari (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
Social security is one of the constitutional rights of citizens, in accordance with article 28 H (3) of the 1945 Constitution of the Republic of Indonesia. The State of Indonesia has changed the social security model several times, ranging from Health Insurance (ASKES) to the latest, namely BPJS. The implementation of BPJS has not been able to solve the problems that arise. The state has a full authority to monopolize the social security with all sanctions that can be imposed if it is not incorporated therein. The question arises as to the idea of delegation of monopoly authority in the provision of social security from before BPJS to BPJS. The rationale is Article 33 verse (2) of the 1945 Constitution and Article 51 of Law Number 5 in the Year of 1999. Keywords: BPJS, Monopoly Authority, Social Security.